The Implementation of Inspiratory Muscle Training to Enhance Weaning from Mechanical Ventilation: A Systematic Literature Review - Anton Priambodo; Henny Suzanna Mediani; Etika Emaliyawati (Palembang MediRose Publisher, 2022)
Background: Mechanical ventilation is very important for the world of critical care. However, the use of mechanical ventilation also affected respiratory muscle weakness. Objective: The purpose of this study was to identify the implementation of Inspiratory muscle training for weaning mechanical ventilation in patients with mechanical ventilation in the Intensive Care Unit. Design: A systematic literature review study design was used. Data Sources: The databases used are CINAHL, PubMed, MEDLINE, Sage Journal, and ScienceDirect. Review Methods: Articles published from 2009-2020 with the type of randomized research-controlled trial (RCT) in English. The keywords